Teacher educators' challenges: focusing on teacher training colleges in Laos - Sengsoulintha, Khampheng (Frontiers in Education, 2025)
Understanding challenges faced by teacher educators further contributes to improvement suggestions on their professional development. It is a pressing study on their working in developing countries where teacher education has experienced reforms to respond to national and international demands. This qualitative study explored the challenges faced by teacher educators in teacher training colleges in Laos. Twenty-three purposively selected participants took part in semi-structured interviews during April–May 2024. Data was analyzed through thematic coding using NVivo-14 software. The analysis identified 23 themes. Detailed data analysis revealed that the primary challenge for teacher educators was their multiple roles or duties and responsibilities, comprising administrative functions and external academic services despite their teaching. That workload led to their difficulties in implementing their role and planning. Furthermore, they encountered challenges in collaboration and planning that impacted task completion. The findings underscore the need for institutional support to help teacher educators manage their workloads more effectively. Future research should: (1). examine how teacher educators manage their multifaceted responsibilities to alleviate work-related stress as a need for a balanced workload approach. Consequently, policymakers and educational leaders may inform their work-related stress and improve the overall quality of teacher training programs. (2). Investigate long-term impacts of administrative overload on teacher educators' wellbeing and retention. (3). Explore policy-level responses to institutional constraints. 4). Conduct comparative studies across regions or teacher education system in the Association of South-East Asian Nations (ASEAN).